Design and implementation of a feedback programmable spin coating system - Ahmed Kadhim; Salah M. Swadi; Ghusoon M Ali (Institute of Advanced Engineering and Science, 2020)
In this work, a speed controlled, the programmable, low-cost, high-efficiency spin coating system is designed and implemented. The system is built from commercially available hard disk drivers DC motor, vacuum pump, speed sensor, brushless driver circuit carries Toshiba's TB6575FNG IC, PIC18F47J53 Microcontroller and using the interactive user interface to communicate with a user. Three different voltage stages and pulse width modulation techniques were used to guarantee accurate spinning speed and time. This system provides a wide range of precise and stable multi-step speeds rang of 1500 to 8,000 rpm. To evaluate the implemented system, ZnO thin films have been deposited by the sol-gel method on a glass substrate. Homogenous and uniform thickness films were obtained. The outstanding features of this system are the stability, accuracy, low energy consumption and durability, and the simplicity of adjusting multi-step spinning speed and time by using the interactive user interface.